2020
DOI: 10.15567/mljekarstvo.2020.0205
|View full text |Cite
|
Sign up to set email alerts
|

The influence of TLR4 gene polymorphisms on milk quality and composition of Lithuanian Holstein cows

Abstract: This study investigated bovine TRL4 gene c.9421C>T, c.2021C>T and c.-10C>T polymorphisms and their relationship with somatic cell count and indicators of milk composition. Blood samples were collected from 152 Lithuanian Holstein dairy cows. The method of polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) was used to genotype TLR4 gene polymorphisms. The data concerning somatic cell count and milk composition indicators (fat, protein, lactose) were analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…infection. On the contrary to the present study, association study by Beecher et al (2010) and Miseikiene et al (2020) determined that there was no association in TLR4 genotypes with SCS in Holstein-Friesian cattle.…”
Section: Resultscontrasting
confidence: 99%
“…infection. On the contrary to the present study, association study by Beecher et al (2010) and Miseikiene et al (2020) determined that there was no association in TLR4 genotypes with SCS in Holstein-Friesian cattle.…”
Section: Resultscontrasting
confidence: 99%
“…The association of the C allele with the milk production traits of Holstein cows was confi rmed in a study by Chen et al (Chen H et al, 2021). At the same time, in the work of other authors, actually parity values of the C and T allele frequencies for this locus were revealed for Lithuanian Holstein cattle (Mišeikienė R et al, 2020). Such differences in the values of allele frequencies may indicate on infl uence of the origin of animals (population factor).…”
Section: Discussionmentioning
confidence: 72%
“…Bilgen et al studied the polymorphism of TLR4 by several marker systems using animals of both commercial and local cattle breeds in Anatolia, Turkey (Bilgen N et al, 2016). In addition to the study of the effect of different mutations in TLR4 gene on the resistance/susceptibility to diseases, there are also recent investigations on their infl uence on economically valuable traits in cattle such as milk production, including milk quality, in different countries (Zhou H et al, 2017;El-Domany WB et al, 2019;Mišeikienė R et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…TLR4 polymorphisms are not associated only with disease resistance/susceptibility but also with somatic cell count (SCC)/SCS (Chen et al, 2022;Mišeikienė et al, 2020;Noori et al, 2013;Roldan-Montes et al, 2020;Sharma et al, 2006a;Wang et al, 2007), milk production traits (Chen et al, 2022;Mišeikienė et al, 2020;Noori et al, 2013;Wang et al, 2018;Zhou et al, 2017), lactation persistency (Sharma et al, 2006a), infectious bovine keratoconjunctivitis (Kataria et al, 2011), and maternal calving difficulty (Mullen et al, 2018). Three studies by Sharma et al (2006aSharma et al ( , 2006bSharma et al ( , 2015, reported the same allele, allele G from the TLR4 c.-226G>C SNP, to be associated with lower SCS, longer lactation persistency and lower risk of MAP infection in Canadian Holstein.…”
Section: T a B L E 1 (Continued)mentioning
confidence: 99%
“…Mastitis, an inflammatory disease of the mammary gland, is the most frequently occurring problem in dairy farms, causing a significant economic loss and a severe impact on animal welfare (Elmagharaby et al, 2018; Yang et al, 2022). The variation in genes controlling the immune response contributes to susceptibility to infections, so more studies are focusing on the genes responsible for innate immunity and their association with mastitis (Badami et al, 2019; Bjelka & Novák, 2020; Elmagharaby et al, 2018; Mišeikienė et al, 2020; Zhou et al, 2017). Pattern recognition receptors play an important role in the innate immune response, as they recognise permanent structures of the microorganisms called pathogen‐associated molecular patterns (PAMPs) and initiate the development of both innate and adaptive immune responses (Badami et al, 2019; Bhaladhare et al, 2019; Blagitz et al, 2015; Elmagharaby et al, 2018; Yang et al, 2022; Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%